2016
DOI: 10.1371/journal.pone.0149453
|View full text |Cite
|
Sign up to set email alerts
|

Half of Pulmonary Tuberculosis Cases Were Left Undiagnosed in Prisons of the Tigray Region of Ethiopia: Implications for Tuberculosis Control

Abstract: IntroductionPrison settings have been often identified as important but neglected reservoirs for TB. This study was designed to determine the prevalence of undiagnosed pulmonary TB and assess the potential risk factors for such TB cases in prisons of the Tigray region.MethodA cross-sectional study was conducted between August 2013 and February 2014 in nine prisons. A standardized symptom-based questionnaire was initially used to identify presumptive TB cases. From each, three consecutive sputum samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 22 publications
2
35
4
1
Order By: Relevance
“…Our estimated TB prevalence falls within the range of figures found in other prison settings across the African continent [ 17 , 18 , 20 27 ]. Importantly, though, this high prevalence was found after 16 years of a program that made TB screening and treatment routinely available in the main prisons of Côte d’Ivoire.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our estimated TB prevalence falls within the range of figures found in other prison settings across the African continent [ 17 , 18 , 20 27 ]. Importantly, though, this high prevalence was found after 16 years of a program that made TB screening and treatment routinely available in the main prisons of Côte d’Ivoire.…”
Section: Discussionsupporting
confidence: 82%
“…Overcrowding is a well known condition for TB transmission in prison [ 16 18 ]. The average living surface area at MACA is 1.3 m 2 per male inmate, well below the 4m 2 recommended by the WHO [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the majority of the PDL in this study did not perform X-ray for diagnosis and only some of them went to the rear services to carry out the examination. This reveals weaknesses in the availability of the equipment and the network for TB screening, which can be caused by the limited financial and human resources present in most penitentiary complexes [10,16]. These results reveal the need to acquire radiological equipment, fixed or mobile, since some studies demonstrate that annual radiological screening, other than symptom-based one, has been used to identify suspected cases of TB and played an important role in the reduction of the disease incidence and prevalence in prisons [11,17].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the PDL receive visits from family, friends and have constant communication with local staff, which make them important sources of the disease, with the risk of dissemination to the population inside and outside of prison [15,16]. Once there is an association between the cases notified by the penitentiary complex and more than ten contacts identified, the investigation of contacts emerges as a strategy to disease control.…”
Section: Discussionmentioning
confidence: 99%